Electrolytic copper foil and preparation method thereof, negative pole piece and secondary battery

By optimizing the crystal structure of the electrolytic copper foil and controlling the ratio of columnar crystals to equiaxed crystals, the average grain boundary angle and the grain size, the problems of insufficient tensile strength, low elongation and poor thermal stability of the existing electrolytic copper foil are solved. High tensile strength, elongation and thermal stability are achieved, improving the performance and reliability of secondary batteries.

CN119361715AActive Publication Date: 2025-01-24JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD

Patent Information

Application Number
CN202411288160.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-24
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing electrolytic copper foils show insufficient tensile strength, low elongation and poor thermal stability in high-quality energy density secondary batteries, resulting in easy strip breakage and wrinkle problems during manufacturing and use.

Method used

By optimizing the crystal structure of copper foil, the ratio of the cylindrical crystal to the axis crystal, the average value of the crystal boundary, and the size of the grains to achieve high tensile strength, extension rate and thermal stability. Specific methods include in the section of the thickness direction of the electrolytic copper foil, adjust the proportional coefficient of the columnar crystal to the axis crystal TJM in the range of 0.2 ≤ TJM ≤ 0.4, control the maximum value of the crystal corner Kammax ≤ 5.5 °, and ensure that it is less than equal to 0.5 The grain ratio of μm reaches more than 95%.

Benefits of technology

The high tensile strength and high elongation of electrolytic copper foil are achieved, and its thermal stability is enhanced, thereby reducing the possibility of band breakage and wrinkles during manufacturing and use, and improving the production efficiency and service life of secondary batteries. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361715A_ABST
    Figure CN119361715A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolytic copper foil and a preparation method thereof, a negative pole piece and a secondary battery. The electrolytic copper foil comprises at least one copper layer, the proportionality coefficient of columnar crystals and isometric crystals in the section of the copper layer in the thickness direction is TJM, the maximum value of the mean value of grain boundary angles is KAMmax, and the grain size is R. The section meets at least one of the following conditions (1)-(3): (1) 0.2 < = TJM < = 0.4; (2) KAMmax is less than or equal to 5.5 degrees; and (3) the proportion of crystal grains with R < = 0.3 [mu] m is 40-50%, the proportion of crystal grains with R < = 0.4 [mu] m is 70-80%, and the proportion of crystal grains with R < = 0.5 [mu] m is greater than or equal to 95%. The electrolytic copper foil has high tensile strength, high elongation and high thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrolytic copper foil and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of new energy technologies, the demand for high-performance secondary batteries is growing. As the core of new energy storage technology, the performance of lithium-ion batteries cannot be improved without high-quality electrode materials. Copper foil is often used as the negative electrode current collector of secondary batteries, which has an important impact on the overall performance and safety of the battery. The copper foil currently used mainly includes rolled copper foil based on the rolling process and electrolytic copper foil based on the electroplating process. The production technology of rolled copper foil is high, the process is complex, and the cost is high. It is not suitable for large-scale production. Therefore, people gradually shift their research focus to electrolytic copper foil. However, in order to meet the current high-quality energy density requirements of secondary batteries, electrolytic copper foil must be thinner and have sufficient tensile elongation and thermal stability. The mechanical properties of existing electrolytic copper foil can no longer meet the requirements of high-quality energy density secondary batteries. Wrinkles and broken belts often occur during the cold pressing process of the negative electrode sheet or during the winding or lamination of the battery and the battery cycle, which greatly affects the production efficiency and service life of the secondary battery. Summary of the invention

[0003] The present application provides an electrolytic copper foil and a preparation method thereof, a negative electrode plate and a secondary battery, the purpose of which is to make the electrolytic copper foil have both high tensile strength and high elongation, and high thermal stability.

[0004] In order to achieve the above object, the first aspect of the present application provides an electrolytic copper foil, comprising at least one copper layer, wherein the ratio coefficient of columnar crystals to equiaxed crystals in the cross section along the thickness direction of the copper layer is T JM , T JM =N (I>1) / N (I≤1) , where N is the number of grains, I is the grain aspect ratio calculated by fitting ellipse in EBSD grain size measurement data, and the maximum value of the mean grain boundary angle in the cross section is KAM max , in, is the grain boundary angle of each grain boundary, n is the total number of grain boundaries, the grain size in the cross section is R, and the cross section satisfies at least one of the following conditions (1) to (3):

[0005] (1)0.2≤T JM ≤0.4;

[0006] (2) KAM max ≤5.5°;

[0007] (3) The proportion of grains with R≤0.3μm is 40% to 50%, the proportion of grains with R≤0.4μm is 70% to 80%, and the proportion of grains with R≤0.5μm is greater than or equal to 95%.

[0008] Therefore, the electrolytic copper foil provided in the present application has both high tensile strength and high elongation, and has high thermal stability, which can effectively reduce the possibility of breakage and / or wrinkling during the manufacturing process of the electrolytic copper foil and / or during the manufacturing and use of secondary batteries.

[0009] In any embodiment of the present application, the copper layer has two surfaces opposite to each other in its own thickness direction, namely a first surface and a second surface, and the surface roughness and / or brightness of the first surface and the second surface are different.

[0010] In any embodiment of the present application, the electrolytic copper foil further includes at least one protective layer. Optionally, the protective layer includes a first protective layer and a second protective layer. The first protective layer is disposed on the first surface, and the second protective layer is disposed on the second surface.

[0011] In any embodiment of the present application, the protective layer comprises at least one of chromium, glucose and nitride;

[0012] Optionally, the protective layer contains chromium. Further optionally, the content of chromium in at least one of the protective layers is 20 ppm to 80 ppm.

[0013] In any embodiment of the present application, the thickness of the first protective layer is 100 nm to 300 nm, and / or the thickness of the second protective layer is 100 nm to 300 nm.

[0014] In any embodiment of the present application, the thickness of the copper layer is 4 μm to 8 μm.

[0015] In any embodiment of the present application, the tensile strength of the electrolytic copper foil at room temperature is 60 kgf / mm 2 ~70kgf / mm 2 , and / or, the elongation of the electrolytic copper foil at room temperature is ≥4.5%, and the room temperature is 10°C to 40°C.

[0016] In any embodiment of the present application, the attenuation rate of the tensile strength of the electrolytic copper foil is Rmi≤3.5%, Rmi=(R m1 -R m2 ) / R m1 *100%, where R m1 and R m2They are respectively the tensile strength of the electrolytic copper foil at room temperature and the tensile strength of the electrolytic copper foil after heat treatment, the room temperature is 10°C to 40°C, and the temperature of the heat treatment is 100°C to 250°C.

[0017] A second aspect of the present application provides a method for preparing an electrolytic copper foil, comprising the following steps:

[0018] Placing an anode and a cathode to be plated in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the electrolyte contains copper ions, sulfuric acid, chloride ions, a leveler, a brightener and a wetting agent;

[0019] Optionally, the concentration of the copper ions in the electrolyte is 70 g / L to 100 g / L;

[0020] Optionally, the concentration of the sulfuric acid in the electrolyte is 80 g / L to 140 g / L;

[0021] Optionally, the mass concentration of the chloride ions in the electrolyte is 10ppm to 25ppm;

[0022] Optionally, the mass concentration of the leveling agent in the electrolyte is 1 ppm to 15 ppm;

[0023] Optionally, the mass concentration of the brightener in the electrolyte is 10ppm to 60ppm;

[0024] Optionally, the mass concentration of the wetting agent in the electrolyte is 5 ppm to 20 ppm.

[0025] In any embodiment of the present application, the leveling agent is a nitrogen-containing compound, optionally including one or more of gelatin, collagen, thiazolidine green, tetrahydrothiothione and polyethyleneimine compounds; and / or,

[0026] The brightener is an organic divalent sulfide, optionally including one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate, bis-(sodium sulfoethyl sulfate)-disulfide and 1,3-propanedisulfonic acid; and / or,

[0027] The wetting agent is a polyether compound, and may optionally include one or more of polyethylene glycol, carboxyethyl cellulose and polyvinyl pyrrolidone.

[0028] In any embodiment of the present application, the temperature of the electrolyte during the electrolysis process is 50°C to 60°C.

[0029] In any embodiment of the present application, the method further comprises the step of placing the electrolytic copper foil in a passivation solution for passivation.

[0030] Optionally, the passivation solution contains one or more of a chromium source, glucose and a nitride.

[0031] A third aspect of the present application provides a negative electrode plate, comprising the electrolytic copper foil described above or the electrolytic copper foil prepared by the described method.

[0032] A fourth aspect of the present application provides a secondary battery, comprising the negative electrode plate.

[0033] A fifth aspect of the present application provides an electrical device comprising at least one of the secondary batteries described above.

[0034] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.

[0035] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0037] Figure 1 EBSD photograph of the cross section of the electrolytic copper foil in the thickness direction of Example 1;

[0038] Figure 2 EBSD photograph of the cross section of the electrolytic copper foil in the thickness direction of Example 2;

[0039] Figure 3 This is an EBSD photograph of a cross section of the electrolytic copper foil of Example 3 along the thickness direction. DETAILED DESCRIPTION

[0040] Below, some embodiments of the electrolytic copper foil and its preparation method, negative electrode sheet, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0041] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0042] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0045] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0046] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0047] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0048] To sum up the background, copper foil with high tensile strength and high elongation can keep the battery in good performance. However, with the current process technology, tensile strength and elongation are negatively correlated, and it is difficult to achieve both. It is difficult to ensure that the tensile strength is improved while the elongation is improved. At the same time, after high-temperature aging, the physical properties of copper foil fluctuate greatly. It is very necessary to develop new electrolytic copper foil that can meet the requirements of high tensile strength, high elongation and high thermal stability.

[0049] In order to achieve the above-mentioned object, the first aspect of the present application provides an electrolytic copper foil, comprising at least one copper layer. The ratio coefficient of columnar crystals to equiaxed crystals in the cross section of the copper layer along the thickness direction is denoted as T JMThe maximum value of the mean grain boundary angle in the cross section of the copper layer along the thickness direction is recorded as KAM max The grain size in the cross section of the copper layer along the thickness direction is denoted as R. The cross section of the copper layer along the thickness direction satisfies at least one of the following conditions (1) to (3):

[0050] (1)0.2≤T JM ≤0.4;

[0051] (2) KAM max ≤5.5°;

[0052] (3) The proportion of grains with R≤0.3μm is 40% to 50%, the proportion of grains with R≤0.4μm is 70% to 80%, and the proportion of grains with R≤0.5μm is greater than or equal to 95%.

[0053] The electrolytic copper foil that meets at least one of the above conditions (1) to (3) has both high tensile strength and high elongation, and has high thermal stability, which can effectively reduce the possibility of breakage and / or wrinkling during the manufacturing process of the electrolytic copper foil and / or during the manufacturing and use of secondary batteries.

[0054] Columnar crystals and equiaxed crystals have meanings known in the art and can be determined and measured by methods known in the art. For example, the morphology of a crystal can be described by a fitted ellipse, wherein the major axis and minor axis of the ellipse correspond to the maximum and minimum dimensions of the crystal, respectively. The aspect ratio of the fitted ellipse (i.e., the ratio of the major axis to the minor axis) can be used to quantify the morphological characteristics of the crystal, such as the aspect ratio of a columnar crystal is generally greater than 1, while the aspect ratio of an equiaxed crystal is close to 1. The aspect ratio of the fitted ellipse of a columnar crystal is generally greater than that of an equiaxed crystal. The growth characteristics of a columnar crystal cause it to grow significantly in a specific direction, while growth in other directions is restricted. The aspect ratio of the fitted ellipse of an equiaxed crystal is close to 1, indicating that its growth in all directions is uniform.

[0055] The ratio coefficient T of columnar crystals to equiaxed crystals in the cross section of the copper layer along the thickness direction JM =N (I>1) / N (I≤1) , where N is the number of grains and I is the grain aspect ratio calculated by fitting ellipse in EBSD grain size measurement data. JMIt can be obtained by measurement methods known in the art, such as using argon gas ionization, bombarding the sample surface under electric field acceleration, and performing physical sputtering under controllable rate conditions by momentum transfer, so as to finely polish the sample surface and obtain a flat profile that meets the EBSD test. The backscattered electrons emitted from the surface of the crystal sample diffract with the sample crystal structure, and the diffraction pattern (EBSP, Electron Backscatter Pattern) formed can reflect the orientation information of the crystal. Through fast image analysis algorithms, EBSD automatically captures highly detailed crystal orientation maps from large sample areas; by comparing the crystal orientation differences of adjacent EBSPs, EBSD can identify grain boundaries. If the crystal orientation difference between two areas exceeds a certain threshold (usually a few degrees), they can be considered to be different grains; by mapping the crystal orientation of the sample surface, a distribution map of the grains can be constructed. By analyzing these distribution maps, the length and width dimensions of the grains can be measured, and the corresponding aspect ratio of the grains can be output. The cross section of the copper layer along the thickness direction has a ratio coefficient of columnar crystals to equiaxed crystals of 0.2 to 0.4, which can achieve both high tensile strength and high elongation of the electrolytic copper foil. As described below, the ratio coefficient T of columnar crystals to equiaxed crystals on the cross section is JM When the ratio is less than 0.2, the electrolytic copper foil has a large number of equiaxed grains, and the equiaxed grains present an isotropic crystal morphology with good plasticity and toughness. In copper foil, the growth of equiaxed grains is usually accompanied by <200> Preferred orientation of crystal directions. This crystal morphology helps to improve the ductility of the material. At the same time, because the structure of equiaxed crystals is uniform, its growth is more conducive to improving the density of twin grain boundaries of the material, which helps to improve ductility, but reduces tensile strength. The crystal structure composed of more equiaxed crystals has poor structural density, is more unstable during the heat treatment of copper foil, and has large fluctuations in the physical properties of copper foil. During battery manufacturing and use, it deforms due to the applied stress and heat, resulting in wrinkling of copper foil. In addition, the ratio coefficient T between columnar crystals and equiaxed crystals on this section is JM When the value is greater than 0.4, the columnar grains of the copper foil occupy more area of ​​the copper foil, the crystal structure of the copper foil is too dense, and the copper foil becomes brittle, thus causing breakage and tearing during battery manufacturing and use.

[0056] The maximum value of the grain boundary angle in the cross section of the copper layer along the thickness direction in, is the grain boundary angle of each grain boundary, and n is the total number of grain boundaries. KAM maxIt can be obtained by measurement methods known in the art, such as using EBSD to identify grain boundaries by analyzing the difference in crystal orientation between adjacent regions. If the orientation difference between two regions exceeds a certain threshold (usually a few degrees), they can be considered to be different grains separated by grain boundaries. This difference can be determined by comparing the crystallographic features of EBSP; EBSD can measure the grain boundary angle, that is, the orientation difference between adjacent grains. The crystal orientation data obtained by EBSD can be used to calculate the grain boundary angle between two adjacent grains at the grain boundary, which is usually expressed by the Euler angle.

[0057] The maximum value of the grain boundary angle KAM in the cross section of the copper layer along the thickness direction max ≤5.5°, the electrolytic copper foil can have both high tensile strength and high elongation. (KAM) is a core point composed of 24 nearest neighboring points, which is used to assign a scalar value to each point to represent its local grain boundary angle. KAM can qualitatively reflect the degree of homogenization of plastic deformation. A higher value indicates a greater degree of plastic deformation or a higher defect density. In the plastic deformation process of the material, uniform deformation helps to improve the tensile elongation properties of the material. In areas with higher KAM values, due to the greater degree of plastic deformation, stress is more likely to concentrate, increasing the probability of crack nucleation and reducing the tensile elongation properties of the material. In the deformation process of the material, areas with higher KAM values ​​indicate that the stability of the crystal structure is poor, which will cause the material to be more prone to local plastic deformation or fracture when subjected to tensile force. The KAM value is also related to the recrystallization behavior of the material. During the heating process after deformation, areas with higher KAM values ​​may be more prone to static recrystallization. During the static recrystallization process, the newly formed grains may gradually grow, causing the grain size distribution of the material to become uneven, which will reduce the strength and toughness of the material. Especially when kept at high temperature for a long time, secondary recrystallization will occur, forming a small amount of large-grained structure, which will further reduce the mechanical properties of the material.

[0058] As described below, the maximum value of the grain boundary angle KAM max When the angle is greater than 5.5°, the crystal structure stability of the copper foil deteriorates, the tensile strength and elongation both deteriorate, and the high-temperature stability decreases, resulting in breakage and / or wrinkling during the manufacturing process of the electrolytic copper foil and / or during the manufacturing and use of secondary batteries.

[0059] The grain size R in the cross section of the copper layer along the thickness direction is characterized by an equivalent circle diameter, which has a well-known meaning in the art. The diameter of a circle equal to the projected area of ​​the grain is the equivalent circle diameter, which can be measured by methods well-known in the art, such as using EBSD technology for single measurement.

[0060] In the cross section of the copper layer along the thickness direction, the proportion of grains with a grain size of R≤0.3μm reaches 40%-50%, the proportion of grains with a grain size of R≤0.4μm is 70%-80%, and the proportion of grains with a grain size of R≤0.5μm is greater than or equal to 95%, which can also achieve electrolytic copper foil with both high tensile strength and high elongation. The tensile strength of copper foil increases with the decrease of grain size. The tensile strength is closely related to the transfer of slip from plastically deformed grains to adjacent grains. Whether this transfer can occur depends mainly on whether the stress concentration generated by the dislocation pile-up group near the grain boundary of the slipped grain can stimulate the dislocation source in the adjacent grain slip system, so that it can start to move and perform coordinated multi-slip. Refining the grains can produce more grain boundaries. If the structure of the grain boundary does not change, a greater external force must be applied to produce dislocation pile-up, thereby strengthening the material. However, too small a grain size may lead to an increase in grain boundaries. As an obstacle to dislocation movement, grain boundaries can improve the strength of the material, but too many grain boundaries may increase the brittleness of the material and reduce its plastic deformation capacity. Too large a grain size may reduce the density of grain boundaries and reduce the strength of the material, especially in the fine grain strengthening effect, where an increase in grain size will weaken this strengthening mechanism. Too large a grain size is also not conducive to the fatigue life of the material, because cracks inside the grains are more likely to expand.

[0061] As described below, in the cross section of the copper layer along the thickness direction, the proportion of grains with a grain size of R≤0.3μm is less than 40%, and / or, the proportion of grains with a grain size of R≤0.4μm is less than 70%, and / or, the proportion of grains with a grain size of R≤0.5μm is less than 95%. The overall grain size of the copper foil is large, the crystal structure is unstable, the tensile strength is low, and the tensile strength is severely attenuated after heat treatment. During the coating and manufacturing process of the secondary battery, the electrolytic copper foil may break due to the pressure applied locally. In the cross section of the copper layer along the thickness direction, the proportion of grains with a grain size of R≤0.3μm is greater than 50%, and / or, the proportion of grains with a grain size of R≤0.4μm is greater than 80%. The overall grain size of the copper foil is small, the electrolytic copper foil is very brittle, and has poor plasticity. It is easy to tear and break during the production process of the electrolytic copper foil, and it is easy to tear at the local bending position during the winding manufacturing process of the negative electrode of the secondary battery.

[0062] The thickness of the copper layer has a well-known meaning in the art and can be measured by methods well-known in the art, such as using the surface density method to test the thickness of the copper foil. The thickness of the copper foil can be calculated by the following formula: Copper foil thickness = copper foil surface density / copper material density. The surface density can be obtained by weighing the mass of a copper foil sample of a certain area (usually 10*10cm), and the density of the copper foil material is obtained by the standard reference value (8.9g / cm 3 ).

[0063] In some embodiments, the thickness of the copper layer is 4 μm to 8 μm. It is understandable that the thickness of the copper layer can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, and any value therebetween or a range between any two values. The copper layer thickness within this range can further increase the capacity of the battery.

[0064] In some embodiments, the copper foil has two surfaces opposite to each other in its thickness direction, namely, a first surface and a second surface, and the surface roughness and / or brightness of the first surface and the second surface are different, which can further improve the elongation of the copper foil. It can be understood that the vertical distance between the first surface and the second surface is the thickness of the copper layer.

[0065] In some embodiments, the electrolytic copper foil further comprises at least one protective layer. Optionally, the protective layer comprises a first protective layer and a second protective layer, the first protective layer being disposed on the first surface, and the second protective layer being disposed on the second surface. The provision of the protective layer can effectively reduce oxidation on the surface of the electrolytic copper foil.

[0066] In some embodiments, the protective layer comprises at least one of chromium, glucose and nitride.

[0067] In some embodiments, the protective layer contains chromium. Further optionally, the content of chromium in the at least one protective layer is 20ppm to 80ppm and any value therebetween or a range between two values, for example, 30ppm, 40ppm, 50ppm, 60ppm, or 70ppm.

[0068] In some embodiments, the thickness of the first protective layer is 100nm to 300nm, and / or the thickness of the second protective layer is 100nm to 300nm. It is understandable that the thickness of the first protective layer can be independently selected from 100nm to 300nm and any value therebetween or a range between two values, for example, it can also be selected from 150nm, 200nm, 250nm; the thickness of the second protective layer can be independently selected from 100nm to 300nm and any value therebetween or a range between two values, for example, it can also be selected from 150nm, 200nm, 250nm.

[0069] In some embodiments, the tensile strength of the electrolytic copper foil at room temperature is 60 kgf / mm 2 ~70kgf / mm 2 And any value between them or a range between two values, for example, it can also be 62kgf / mm 2 、64kgf / mm 2 、66kgf / mm 2 、68kgf / mm 2 The normal temperature is 10°C to 40°C.

[0070] In some embodiments, the elongation of the electrolytic copper foil at room temperature is ≥ 4.5%, and the room temperature is 10°C to 40°C.

[0071] In some embodiments, the attenuation rate of the tensile strength of the electrolytic copper foil is Rmi≤3.5%, Rmi=(R m1 -R m2 ) / R m1 *100%, where R m1 and R m2 They are respectively the tensile strength of the electrolytic copper foil at room temperature and the tensile strength of the electrolytic copper foil after heat treatment, the room temperature is 10°C to 40°C, and the heat treatment temperature is 100°C to 250°C. In some embodiments, the heat treatment comprises heating the electrolytic copper foil to 250°C at a rate of 5°C / min, heat treating at 250°C for 2 hours, and then cooling to room temperature (25°C) at a rate of 5°C / min. The attenuation rate Rmi of the tensile strength of the electrolytic copper foil within this range can further reduce the risk of breaking and / or wrinkling of the electrolytic copper foil during the manufacturing process and / or during the manufacturing and use of the secondary battery.

[0072] Electrolytic copper foil will undergo high-temperature aging during the post-processing process. At the same time, it will undergo a long-term high-temperature process during the battery manufacturing process and the use of secondary batteries. The high-temperature tensile strength decay of electrolytic copper foil has a significant impact on these processes. The tensile strength of copper foil after heat treatment directly affects its performance as a negative electrode current collector of lithium batteries. The reduction in tensile strength will lead to a decrease in the mechanical stability of the battery during the charging and discharging process, affecting the cycle life and safety of the battery. In the manufacturing process of battery electrodes, copper foil needs to be compounded with other materials as a current collector. The reduction in tensile strength will affect the bonding strength of copper foil and other materials, and thus affect the overall performance of the electrode. During the battery assembly process, the reduction in the tensile strength of copper foil also affects the structural stability of the battery. If the tensile strength of copper foil decays too quickly, it will cause cracks or breaks in the battery during assembly or use, affecting the reliability of the battery.

[0073] As described below, the attenuation rate Rmi of the tensile strength of the electrolytic copper foil is greater than 3.5%, which will lead to a large difference in the consistency of the tensile strength of the electrolytic copper foil during the manufacturing process and / or during the manufacturing and use of the secondary battery, increase the risk of broken strips and deterioration of electrode performance, and cause secondary battery safety problems.

[0074] The second aspect of the present application provides a method for preparing an electrolytic copper foil, comprising the following steps:

[0075] The anode and the cathode to be plated are placed in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the electrolyte contains copper ions, sulfuric acid, chloride ions, a leveler, a brightener and a wetting agent.

[0076] In some embodiments, the concentration of copper ions in the electrolyte is 70 g / L to 100 g / L and any value therebetween or a range between any two values, for example, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L. When the copper ion concentration is within this range, electrolysis can be performed at a high current density to improve the electrolysis efficiency. When the copper ion concentration is high, copper sulfate is easily precipitated. When the copper ion concentration is low, the electrolyte conductivity is low, the current density is also reduced, and the electrolysis efficiency is low.

[0077] During the preparation of the electrolyte, the source of copper ions may be a copper salt, such as copper sulfate.

[0078] In some embodiments, the concentration of sulfuric acid in the electrolyte is 80 g / L to 140 g / L and any value therebetween or a range between any two values, for example, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L. When the concentration of sulfuric acid is high, the solubility of copper sulfate in the electrolyte is reduced, and it is easy to crystallize and precipitate at the anode, hindering the normal dissolution process of the anode and causing anode passivation. When the concentration of sulfuric acid is low, the anode is also easily passivated. The concentration of sulfuric acid within this suitable range is more conducive to electroplating.

[0079] In some embodiments, the mass concentration of chloride ions in the electrolyte is 10ppm to 25ppm and any value therebetween or a range between any two values, for example, 12ppm, 15ppm, 20ppm, 22ppm. Chloride ions can reduce anode polarization, eliminate plating stripes in high current density areas, promote the deposition of copper ions, increase cathode polarization, and thus affect the surface brightness of electrolytic copper foil. Chloride ions can also react with Cu, an intermediate product of copper electrodeposition. + A special chemical reaction occurs, which is closely related to the surface morphology and pimple defects of the copper plating. When the concentration of chloride ions is within this range, the surface roughness of the copper plating can be further reduced and the burrs can be reduced. The copper plating has better leveling performance and brightness. In addition, it can also solve the problem of accelerated corrosion of equipment.

[0080] During the preparation of the electrolyte, the source of chloride ions may be hydrochloric acid, sodium chloride or potassium chloride.

[0081] In some embodiments, the mass concentration of the leveler in the electrolyte is 1ppm to 15ppm and any value therebetween or a range between any two values, for example, 5ppm, 8ppm, 10ppm, 12ppm. The leveler can smooth the microscopic profile of the copper plating surface and reduce the surface roughness. Optionally, the leveler is a nitrogen-containing compound, and further optionally, the leveler includes one or more of gelatin, collagen, thiazolidine green, tetrahydrothiothione and polyethyleneimine compounds.

[0082] In some embodiments, the mass concentration of the brightener in the electrolyte is 10ppm to 60ppm and any value therebetween or a range between any two values, for example, 20ppm, 30ppm, 40ppm, 50ppm. The brightener can promote grain nucleation, produce the effect of grain refinement, and achieve a matte bright effect. Optionally, the brightener is an organic divalent sulfide, and further optionally the brightener includes one or more of 3-mercapto-1-propane sulfonate sodium (English abbreviation MPS), polydisulfide dipropane sulfonate sodium (English abbreviation SPS), bis-(sodium sulfoethyl sulfate)-disulfide (English abbreviation SES) and 1,3-propanedisulfonic acid (English abbreviation PDS).

[0083] In some embodiments, the mass concentration of the wetting agent in the electrolyte is 5ppm to 20ppm and any value therebetween or a range between any two values, for example, 8ppm, 10ppm, 12ppm, 15ppm, 18ppm. The wetting agent reduces the surface tension of the electrode / solution interface, promotes the escape of bubbles, and prevents defects such as pinholes. At the same time, the wetting agent can be directionally adsorbed on the electrode surface, improve cathode polarization, inhibit the deposition rate of copper ions, and make the coating crystal more delicate and compact.

[0084] Chloride ions have a synergistic effect with levelers, brighteners, and wetting agents, and together affect the crystal structure of the copper plating layer. Optionally, the wetting agent is a polyether compound, and further optionally, the wetting agent includes one or more of polyethylene glycol (PEG), carboxyethyl cellulose (HEC), and polyvinylpyrrolidone (PVP).

[0085] In some embodiments, the temperature of the electrolyte during the electrolysis process is 50°C to 60°C.

[0086] In some embodiments, the anode is a titanium substrate. Optionally, a precious metal coating, such as iridium or tantalum, may be provided on the surface of the titanium substrate.

[0087] In some embodiments, the cathode is a cathode roller, and the surface material of the cathode roller may be high-purity titanium.

[0088] In some embodiments, the method further comprises the step of passivating the electrolytic copper foil in a passivation solution. Optionally, the passivation solution contains one or more of a chromium source, glucose and a nitride.

[0089] Furthermore, in some embodiments, the method further comprises one or more steps of stripping the copper coating from the cathode, washing, drying, and coiling.

[0090] In addition, the secondary battery and the electric device of the present application will be described as appropriate below.

[0091] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0092] Positive electrode

[0093] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0094] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0095] In some of the embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art.

[0096] It should be noted that the secondary battery of the present application may be a lithium ion battery or a sodium ion battery.

[0097] As a non-limiting example of a lithium-ion battery, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds. Non-limiting examples of lithium-containing phosphates of olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.8 Co 0.15 Al 0.05 O2.

[0098] As the sodium ion active material, at least one or more of the following materials may be included: at least one or more of sodium transition metal oxides, polyanionic compounds and Prussian blue compounds. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0099] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. A non-limiting example of the sodium transition metal oxide may be NaxMO2, where M may include one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.

[0100] As a non-limiting example of a sodium ion battery, the positive electrode active material may include one or more of the following materials: one or more of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0101] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0102] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0103] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000 to 25000 mPa·s. When the positive electrode slurry is applied, the coating unit surface density based on dry weight (excluding solvent) can be 15 to 35 mg / cm 2 The compaction density of the positive electrode sheet can be 3.0 to 3.6 g / cm3 , can be selected as 3.3~3.5g / cm 3 .

[0104] Negative electrode

[0105] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0106] In the present application, the negative electrode current collector adopts the electrolytic copper foil of the first aspect of the present application or the electrolytic copper foil prepared by the method of the second aspect of the present application. In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0107] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0108] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0109] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0110] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s to 10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 ~220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .

[0111] Electrolytes

[0112] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0113] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0114] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0115] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0116] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0117] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0118] Isolation film

[0119] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0120] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0121] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.

[0122] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0123] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0124] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0125] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0126] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0127] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.

[0128] In some embodiments, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly through a winding process or a lamination process. The electrode assembly is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly. The number of electrode assemblies contained in the battery cell can be one or more, and those skilled in the art can select according to actual needs.

[0129] The secondary battery may be a battery module or a battery pack.

[0130] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0131] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0132] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0133] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0134] As an example, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the secondary battery, a battery pack or a battery module may be used.

[0135] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0136] Example

[0137] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0138] Example 1

[0139] 1) Prepare electrolyte

[0140] Dissolve copper sulfate, sulfuric acid, sodium chloride, leveling agent, brightener and wetting agent in water and stir and mix them evenly. The concentrations of the components are: 80 g / L copper ion, 110 g / L sulfuric acid, 13 ppm chloride ion, 45 ppm MPS (sodium 3-mercapto-1-propane sulfonate) and 35 ppm SPS (sodium polydisulfide propane sulfonate), 7 ppm gelatin and 10 ppm tetrahydrothiazolidinethione, and 14 ppm HEC (carboxyethyl cellulose).

[0141] 2) Electrolysis

[0142] Immerse the anode plate and the cathode roller to be plated in the above electrolyte. The electrolyte temperature is 50°C and the electrolyte flow rate is 40m 3 / h, the cathode roller rotates at a constant speed, and the copper in the solution is deposited on the surface of the cathode roller to form copper foil. The thickness of the copper foil is controlled by the cathode current density and the rotation speed of the cathode roller. Those skilled in the art can use conventional methods to control the current density and the rotation speed of the cathode roller to obtain the target thickness of the copper foil. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, washed, dried, and coiled to form electrolytic copper foil.

[0143] Embodiments 2 to 7

[0144] The method is basically the same as Example 1, except that the relevant parameters in the electrolysis process are adjusted, as shown in Table 1 for details.

[0145] Comparative Examples 1 to 8

[0146] The method is basically the same as Example 1, except that the relevant parameters in the electrolysis process are adjusted, as shown in Table 1 for details.

[0147] Test Section

[0148] 1) Electrolytic copper foil T JM (have the same meaning as above), KAM max (has the same meaning as above), R (has the same meaning as above) test

[0149] The relevant microstructures of the samples of each embodiment and comparative example were observed by electron backscatter diffraction (EBSD), specifically using a C-Swift EBSD detector manufactured by Oxford Instruments, UK, and then the T of each embodiment and comparative example was obtained by using the relevant data and relevant calculation formulas obtained by this method. JM 、KAM max And R value. Among them, the sample is a cross section of the electrolytic copper foil along the thickness direction.

[0150] 2) Tensile strength and elongation test of electrolytic copper foil

[0151] According to the test method GB / T29847-2013, the room temperature tensile strength, tensile strength after heat treatment and elongation of the copper foil were tested at room temperature (about 25°C) using the HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. Among them, the heat treatment is to heat the electrolytic copper foil to 250°C at a speed of 5°C / min, heat it at 250°C for 2 hours, and then cool it to room temperature (25°C) at a speed of 5°C / min. Rmi=(R m1 -R m2 ) / R m1 *100%, where R m1 and R m2 They are respectively the tensile strength of electrolytic copper foil at room temperature and the tensile strength of electrolytic copper foil after heat treatment.

[0152] Table 1

[0153]

[0154]

[0155] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.

[0156] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electrolytic copper foil, characterized in that: The invention comprises at least one copper layer, wherein the ratio coefficient of columnar crystals to equiaxed crystals in the cross section along the thickness direction of the copper layer is T JM , T JM =N (I>1) / N (I≤1) , where N is the number of grains, I is the grain aspect ratio calculated by fitting ellipse in EBSD grain size measurement data, and the maximum value of the mean grain boundary angle in the cross section is KAM max , in, is the grain boundary angle of each grain boundary, n is the total number of grain boundaries, the grain size in the cross section is R, and the cross section satisfies at least one of the following conditions (1) to (3): (1)0.2≤T JM ≤0.4; (2)KAM max ≤5.5°; (3) The proportion of grains with R≤0.3μm is 40% to 50%, the proportion of grains with R≤0.4μm is 70% to 80%, and the proportion of grains with R≤0.5μm is greater than or equal to 95%.

2. The electrolytic copper foil according to claim 1, characterized in that: The copper layer has two surfaces opposite to each other in its thickness direction, namely a first surface and a second surface. The first surface and the second surface have different surface roughness and / or brightness.

3. The electrolytic copper foil according to claim 2, characterized in that: It also includes at least one protective layer. Optionally, the protective layer includes a first protective layer and a second protective layer. The first protective layer is arranged on the first surface, and the second protective layer is arranged on the second surface.

4. The electrolytic copper foil according to claim 3, characterized in that: The protective layer comprises at least one of chromium, glucose and nitride; Optionally, the protective layer contains chromium. Further optionally, the content of chromium in at least one of the protective layers is 20 ppm to 80 ppm.

5. The electrolytic copper foil according to claim 3, characterized in that: The thickness of the first protective layer is 100 nm to 300 nm, and / or the thickness of the second protective layer is 100 nm to 300 nm.

6. The electrolytic copper foil according to claim 1, characterized in that: The copper layer has a thickness of 4 μm to 8 μm.

7. The electrolytic copper foil according to any one of claims 1 to 6, characterized in that: The tensile strength of the electrolytic copper foil at room temperature is 60kgf / mm 2 ~70kgf / mm 2 , and / or, the elongation of the electrolytic copper foil at room temperature is ≥4.5%, and the room temperature is 10°C to 40°C.

8. The electrolytic copper foil according to any one of claims 1 to 6, characterized in that: The attenuation rate of the tensile strength of the electrolytic copper foil is Rmi≤3.5%, Rmi=(R m1 -R m2 ) / R m1 *100%, where R m1 and R m2 They are respectively the tensile strength of the electrolytic copper foil at room temperature and the tensile strength of the electrolytic copper foil after heat treatment, the room temperature is 10°C to 40°C, and the temperature of the heat treatment is 100°C to 250°C.

9. A method for preparing an electrolytic copper foil, characterized in that: The steps include: Placing an anode and a cathode to be plated in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the electrolyte contains copper ions, sulfuric acid, chloride ions, a leveler, a brightener and a wetting agent; Optionally, the concentration of the copper ions in the electrolyte is 70 g / L to 100 g / L; Optionally, the concentration of the sulfuric acid in the electrolyte is 80 g / L to 140 g / L; Optionally, the mass concentration of the chloride ions in the electrolyte is 10ppm to 25ppm; Optionally, the mass concentration of the leveling agent in the electrolyte is 1 ppm to 15 ppm; Optionally, the mass concentration of the brightener in the electrolyte is 10ppm to 60ppm; Optionally, the mass concentration of the wetting agent in the electrolyte is 5 ppm to 20 ppm.

10. The method for preparing an electrolytic copper foil according to claim 9, characterized in that: The leveling agent is a nitrogen-containing compound, optionally including one or more of gelatin, collagen, thiazolidine green, tetrahydrothiothione and polyethyleneimine compounds; and / or, The brightener is an organic divalent sulfide, optionally including one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate, bis-(sodium sulfoethyl sulfate)-disulfide and 1,3-propanedisulfonic acid; and / or, The wetting agent is a polyether compound, and may optionally include one or more of polyethylene glycol, carboxyethyl cellulose and polyvinyl pyrrolidone.

11. The method for preparing an electrolytic copper foil according to claim 9, characterized in that: The temperature of the electrolyte during the electrolysis process is 50°C to 60°C.

12. The method for preparing an electrolytic copper foil according to claim 9, characterized in that: The invention also includes the step of placing the electrolytic copper foil in a passivation solution for passivation. Optionally, the passivation solution contains one or more of a chromium source, glucose and a nitride.

13. A negative electrode plate, characterized in that: The invention comprises the electrolytic copper foil according to any one of claims 1 to 8, and the electrolytic copper foil prepared according to any one of claims 9 to 12.

14. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 13.

15. An electrical device, characterized in that: Comprising at least one of the secondary batteries described in claim 14.

Citation Information

Patent Citations

  • High product of strength and elongation alloy steel in columnar crystal / isometric crystal composite crystal structure and preparation method thereof

    CN103866179A

  • Copper foil and current collector of energy storage device

    CN110894615A

  • Electrolytic copper foil, method for producing the same, and lithium ion secondary battery

    CN111864177A

  • Electrolyte for manufacturing electrolyte copper foil and application of electrolyte

    CN114182310A

  • High-strength electrolytic copper foil, method for producing same, electrode, and secondary battery

    CN114318427A

Cited By

  • Electrolytic copper foil and preparation method therefor, negative electrode sheet, and secondary battery

    WO2026055929A1

  • Current collector, battery cell, battery device, and electric device

    WO2026170692A1